2010
DOI: 10.1186/1472-6882-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of a sub-fraction of dichloromethane extract of Strobilanthes crispus on human breast and prostate cancer cells in vitro

Abstract: BackgroundThe leaves of Strobilanthes crispus (S. crispus) which is native to the regions of Madagascar to the Malay Archipelago, are used in folk medicine for their antidiabetic, diuretic, anticancer and blood pressure lowering properties. Crude extracts of this plant have been found to be cytotoxic to human cancer cell lines and protective against chemically-induced hepatocarcinogenesis in rats. In this study, the cytotoxicity of various sub-fractions of dichloromethane extract isolated from the leaves of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 27 publications
6
66
1
Order By: Relevance
“…Cancer is a major public health problem worldwide with millions of new cancer patients diagnosed each year and many deaths resulting from this disease (Barbaric et al, 2010;Yaacob et al, 2010). Breast cancer is the second most diagnosed cancer worldwide with a total of 1.38 million cases (Cleary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a major public health problem worldwide with millions of new cancer patients diagnosed each year and many deaths resulting from this disease (Barbaric et al, 2010;Yaacob et al, 2010). Breast cancer is the second most diagnosed cancer worldwide with a total of 1.38 million cases (Cleary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that S. crispa leaves possess anti-diabetic, diuretic and blood pressure lowering properties (17). Furthermore, a number of studies have recorded the potency of S. crispa extracts in inhibiting cancer cell growth (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the effects of phytochemicals on TP53 gene expression as a measure of apoptosis induction in cell lines (Azizi et al, 2009;Yaacob et al, 2010;Wang and Sun, 2010;Alshatwi et al, 2011;Alshehri and Elsayed, 2012). It is well known that p53 acts biochemically as a transcription factor and biologically as a powerful tumor suppressor.…”
Section: Resultsmentioning
confidence: 99%